Of Ink and Clay: Tattooed Mummified Human Remains and Female Figurines from Deir el-Medina. Issue 1 (June 2022) - Austin, Anne; Arnette, Marie-Lys
This article offers the first publication of the mummified remains of two tattooed women in conjunction with three unpublished figurines with tattoo motifs from Deir el-Medina. Several recurrent motifs are shared between these women and the figurines, including the use of Bes-images, Nilotic elements, and points at the neck. These themes also appear in previously published tattooed figurines, so-called cosmetic spoons, and paintings. In some cases, the figurines and the women even share the same location of the tattoos on their body, suggesting that the combined location and tattoo motifs are integral to their function and/or meaning. Through linking tattooing on human remains with figurines, our work evaluates when we can interpret markings on figurines as tattooing while also exploring potential explanations for the tattoo motifs. To do so, we connect these new examples with texts and material culture that would have been accessible to the people of Deir el-Medina.